La coroplastica di Lemno tra l’età orientalizzante e la fine dell’età arcaica - Sarcone, Germano (O T I V M, 2024)
The island of Lemnos was a hub of uninterrupted maritime trade from the Bronze Age to the Archaic Period in the North Aegean. In the mythological tradition, Lemnos is mentioned as the island of the god Hephaestus, and this connection with the metalworker god denotes the island’s importance as a craft centre. On this island an original coroplastic production flourished alongside a rich and continuous ceramic production from the Early Iron Age to the Archaic period. This coroplastic production, subject of the present contribution, includes statues, models of buildings and other types, intended for both places of worship and necropolis.